(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article deals with the formation of basic competencies when teaching a biophysics course. The types, functions, pedagogical and psychological qualities of the basic competencies on which they are based are substantiated.